Investigation of Erodibility and Sedimentation in Goyjah Bel basin (Revista Geoaraguaia, 2021)
Goyjah Bel basin is located 10 km south of Ahar city with an area of ​​about 7462.8 hectares, where the occurrence of erosion is remarkable. This study is based on library studies, field studies, and the use of empirical models of erosion and sedimentation estimation. For estimation of the intensity of erosion in these units, and classification of lands based on quantitative criteria, PSIAC method is used with a comprehensive view of all the determinants. Estimation of erosion by this method in geomorphological units proves that the hypotheses on speed and accuracy, identification of the most important erosion factors and the most critical areas of sedimentation, and determination of relations and distribution of erosion in the region is correct. Here, the experimental MPSIAC model, which considers the most effective parameters in erosion and sedimentation, is used, and environmental parameters are evaluated. Finally, the results are compared with neuro-fuzzy model. The results indicate that MPSIAC model works good in this basin. It should be noted that the estimated sediment is in erosion class of 4, and in terms of qualitative classification, the erosion was in a high class. Therefore, according to the definition of this class, it can be said that in this basin, the transfer of soil particles is to an extent that implementation of soil and water conservation programs is necessary and prior, and the use of land must be so limited